Comparative study of treadmill test positive patients with coronary artery profile on coronary angiography in patient presenting with chest pain in BPKIHS, Dharan, Nepal - Gyawali, Achyut; Karki, Prahlad; Pandey, Naveen Kumar; Pandey, Brijesh; Shrestha, Sanjay; Thapa, Rajan; Shrestha, Binam; Gupta, Payal; Mandal, Rajesh Kumar; Neupane, Nilisha (Nepal Mediciti Medical Journal, 2023)
BACKGROUND Diagnosis of Coronary artery disease by Coronary artery angiography is limited by its availability, cost and as an invasive procedure. Treadmill test is a noninvasive and easily available test for diagnosing as well as prognosis of coronary artery disease and is most commonly performed stress test for diagnosis of coronary artery disease. Treadmill test is often used as an initial assessment of patient with suspected coronary artery disease serving as a poor man’s angiogram METHODS This was a cross sectional observational study carried out over a period from 25th August 2023 to 25th November 2023 in Department of Cardiology. A total of 100 patients with positive Treadmill test underwent CAG and subsequently analyzed for the presence of CAD were enrolled in the study. TMT test was done using Bruce Protocol and results were classified as positive and negative upon ECG changes. Data about Socio demographic profiles, clinical data, major comorbidity, the presumed risk factor for CAD were entered in MS Excel and analyzed through SPSS 25. RESULTS A total of 100 patients were enrolled in the study. Males were 45(45%) and females were 55(55%). The mean age of the patient was 53.38±16.7 years and 44.27±13.8 years in male and female group respectively. Smoking (82%) was the number one risk factor in male group and Hypertension (52%) in female group.. Significant CAD was seen in 33% of cases ad normal coronaries in 45%. The most common coronary artery involved having significant disease during coronary angiogram was LAD in 25% of cases CONCLUSIONS There was a significant correlation between positive TMT Results and coronary artery disease in coronary angiography.